4-Cyanopyridine complexes [MX2(4-CNpy)x]n (with X = Cl, Br and x = 1, 2): crystal structures, thermal properties and a comparison with [MX2(3-CNpy)x]n complexes. Issue 11 (27th February 2020) - Heine, Miriam; Fink, Lothar; Schmidt, Martin U.
Abstract : Crystal structures of [MX2 (4-CNpy) x ] with X = Cl and Br, M = Mn, Fe, Co, Ni, Cu, and Zn, and x = 1 and 2 were determined by X-ray powder diffraction. 4-Cyanopyridine can build chain and net structures. Abstract : Eleven new complexes [MX2 (4-CNpy) x ]( n ) with M = Mn, Fe, Co, Ni, Cu, and Zn, X = Cl and Br, 4-CNpy = 4-cyanopyridine, and x = 1 and 2 have been prepared and their structures were characterized by X-ray powder diffraction (XRPD). The reaction of the transition metal halides MX2 (M = Mn, Fe, Co, Ni, Cu and X = Cl, Br) with 4-CNpy leads to the formation of coordination compounds with the composition [MX2 (4-CNpy)2 ] n first. In all these compounds, the metal atoms are octahedrally coordinated by four halogen atoms and two 4-CNpy ligands. The halogen atoms bridge the metal atoms, leading to infinite [MX2 ] n chains. The 4-CNpy molecules coordinate through their pyridine N atoms (Npy ) and form lateral "wings" on the [MX2 ] n chains. The manganese compound [MnBr2 (4-CNpy)2 ] n shows polymorphism with a fully reversible phase transition. The thermal behaviour of compounds [MX2 (4-CNpy)2 ]( n ) was investigated by a combined differential thermal and thermogravimetric analysis (DTA–TG). DTA results show that thermal annealing of [MX2 (4-CNpy)2 ] n at around 240–260 °C leads to compounds of composition [MX2 (4-CNpy)1 ] n (M = Mn, Fe, Co and X = Cl, Br). In these compounds, 4-CNpy acts as a bidentate ligand: the Npy and NCN atoms both coordinate to the metal atoms, building (nearly) linear M-py-CN–M bridges between the [MX2 ] n chains. This results in two-dimensional (2D) networks, which form the layer structures of the [MX2 (4-CNpy)1 ] n compounds. In all bromo compounds [MBr2 (4-CNpy)1 ] n, the 4-CNpy bridges exhibit a head-to-tail-disorder with an inverted orientation of the 4-CNpy molecules between the metal atoms. Further heating of [MX2 (4-CNpy)1 ] n leads to [MnBr2 (4-CNpy)1/2 ] n, [FeCl2 (4-CNpy)1/3 ] n, [CoCl2 (4-CNpy)1/3 ] n and [CoBr2 (4-CNpy)1/3 ] n but their structures could not be determined yet. Additionally, the zinc compound [ZnBr2 (4-CNpy)2 ] was prepared. In its both polymorphs, the Zn atoms are tetrahedrally coordinated by two bromine atoms and two 4-CNpy ligands ( via the Npy atoms) to form discrete complexes. Upon heating to 240 °C, the Zn compound decomposes to ZnBr2 without forming intermediate phases. In all compounds [MX2 (4-CNpy) x ]( n ), the coordination behavior of the 4-CNpy ligand was investigated by infrared (IR) spectroscopy. A comparison with the structures of the corresponding 3-CNpy compounds is given. This article aims at emphasizing the versatile ability of cyanopyridine to act as a mono- or bidentate ligand to build structures with isolated complexes, chains, double chains and planar or wavy 2D networks.